Peran Tgk. Muhammad Daud Beureueh Dalam Pengembangan Pendidikan Islam Di Aceh - Sibhgatullah Ar Rasyid; Suparwany; Nurul Jeumpa (JKA, 2024)
This study discusses the role of Tgk. Muhammad Daud Beureueh, an influential scholar and political leader in Aceh, in the development and renewal of the Islamic education system in the province during his leadership. Using historical approach and descriptive-analytical method, this study found that Tgk. Muhammad Daud Beureueh played an important role in establishing and developing pesantren networks, spreading Islamic education reform ideas, and maintaining the traditional Islamic education system in Aceh. His role in the development of Islamic education in Aceh is also inseparable from his involvement in political movements, especially the Darul Islam/Tentara Islam Indonesia rebellion.